Epidermal growth factor as a potential prognostic and predictive biomarker of response to platinum-based chemotherapy. - Margot Geens; Sofie Stappers; Heleen Konings; Benedicte Y De Winter; Pol Specenier; Jan P Van Meerbeeck; Gert A Verpooten; Steven Abrams; Annelies Janssens; Marc Peeters; Paul Van de Heyning; Olivier M Vanderveken; et al. (PLoS ONE)
In this study, we investigated serum epidermal growth factor (EGF) in an oncological population of head- and neck and pulmonary neoplasms and whether serum EGF could serve as a prognostic marker of survival and as a predictive marker for treatment response to platinum-based chemotherapy. A total of 59 oncological patients and a control group of age- and sex-matched healthy volunteers were included in this study. Pre-treatment serum EGF from both groups was determined. Patient's and tumour characteristics and mortality were recorded during a 5-year follow up period. Baseline serum EGF significantly differed between the oncological patients and the healthy volunteers (p<0.001). Serum EGF was associated with lymph node metastasis (p = 0.004) but not with sex (p = 0.753), age (p = 1.00), TNM stage (p = 0.191) or tumour size (p = 0.077). Neither serum EGF (p = 0.81) nor age (p = 0.55) showed an effect on the patient's survival. Tumour location was significantly associated with overall 5-year survival (p = 0.003). The predictive capacity of serum EGF of response to chemotherapy was limited (AUC = 0.606), a sensitivity of 80% and a specificity of 56% was observed resulting in a likelihood ratio of a positive and negative test equal to 1.81 and 0.36, respectively. In conclusion, serum EGF levels are 5.5 times higher in an oncological population compared to a control group. Within the oncological population, low serum EGF values are associated with the presence of lymph node metastasis. Further investigation is necessary to determine if the serum EGF levels could serve as a diagnostic biomarker.